(untitled) (Journal of Engineering, 2025)
Recently, implantable antennas have gained prominence in biomedical research owing to their compact design and efficient performance and extensive potential in biomedical and wireless communication applications. One such application is in the biomedical field, where the designed system must function within human body tissues and interact with an external device. To implement this communication framework, both advanced software and proper hardware design are essential. The antenna that is designed for biomedical applications must fulfill several requirements including energy efficiency, compact size, and multi-band operations. Therefore, designing an antenna with large bandwidth, multiband capability, circular polarization, and a compact size is essential for medical applications. From that point of view, this paper aims to survey existing antenna designs in literature for implantable medical devices (IMDs). The review conducted in this paper will specifically focus on three types of implantable antennas which are dual-band, circular polarized, and multi-band circular polarized antennas. Besides, we analyze the results of the most recently published articles and compare them with existing literature. The key challenges faced in implantable antenna design will also be discussed in detail.